2014
DOI: 10.1021/jo500029f
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Optical Properties of Tris(trimethylsilyl)silylated Oligothiophene Derivatives

Abstract: The structures and optical properties of tris(trimethylsilyl)silylated oligothiophenes were examined by spectroscopies, theoretical calculations, and single-crystal X-ray measurements. Bathochromic shift from the original oligothiophenes was observed in the tris(trimethylsilyl)silylated ones, confirming the σ-π conjugation between Si-Si σ bonds and π-orbital. 5,5'-Bis(tris(trimethylsilyl)silyl)-2,2'-bithiophene (Si-T2) showed the highest fluorescence quantum yield (ΦF) both in solution (0.67, excited at 350 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…The physicochemical properties of key heteropentalenes are strongly affected by the nature of the heteroatom(s), 23 25 as exemplified by the energies of FMO, and energy of HOMO–LUMO gaps presented in Figure 3 . 26 In principle, their absorption maxima are located around 250 nm whereas emission was investigated only in several cases, e.g., λ em (TT) = 291 nm and λ em (PS) = 266 nm.…”
Section: General Physicochemical Propertiesmentioning
confidence: 99%
“…The physicochemical properties of key heteropentalenes are strongly affected by the nature of the heteroatom(s), 23 25 as exemplified by the energies of FMO, and energy of HOMO–LUMO gaps presented in Figure 3 . 26 In principle, their absorption maxima are located around 250 nm whereas emission was investigated only in several cases, e.g., λ em (TT) = 291 nm and λ em (PS) = 266 nm.…”
Section: General Physicochemical Propertiesmentioning
confidence: 99%
“…We recently investigated aromatic compounds connected with disilanylene groups (-SiR 2 SiR 2 -) [24][25][26][27][28][29][30][31][32][33]. Disilanylene-linkers extend the conjugated system through σ-π interaction, similarly to C=C double bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Chemical structures that combine aSi À Si s bond and an aromatic ring give s-p conjugation resulted in unique optical and electrochemical properties. [6] Molecular design can prevent p-p stacking detrimental to solid-state emission. We have demonstrated that disilane-bridged donor-acceptor molecules displayed intense luminescence in the solid state and explored their applicability as luminophores for OLEDs.…”
Section: Introductionmentioning
confidence: 99%